PELAKSANAAN LELANG TANPA PEMBERITAHUAN PADA PIHAK KETIGA PEMBERI JAMINAN PADA PUTUSAN MA NO. 1497k/Pdt/2001 - Rudy Hartono; Miranda Lumban Tobing; Lidia Novianti Sidabutar; Hakiket Singh Deol (Jurnal Interpretasi Hukum, 2025)
An agreement has clauses that are formed through agreement between interested parties, as well as lending and borrowing activities involving an agreement and cooperation between creditors and debtors. Banking as a creditor adheres to the principles of trust and prudence in providing credit facilities to debtors or customers. The presence of mortgage rights or collateral objects functions to reduce the risk of bad credit. So that banks as recipients of mortgage rights have the authority to carry out parate executions or submit auction requests through Pengadilan Negeri. However, in its implementation, errors, inappropriateness and non-compliance with the law often occur in complying with applicable regulations. This research uses a normative juridical approach with a study method that focuses on the application of law in society. This research uses source collection through literature study and applicable laws and regulations. By describing phenomena or cases that occur in the field in depth, as well as analyzing cause and effect and influencing factors. The results of the research show that there were errors or errors in the implementation of auctions or sales in public which were detrimental to the mortgage rights giver. Carrying out an auction that ignores the applicable instructions and provisions causes losses to the third party giving the mortgage rights. The enactment of Law no. 4 of 1996 Tentang Hak Tanggungan Atas Tanah Beserta Benda-benda Yang Berkaitan Dengan Tanah provides certainty and justice, and gives the creditor the right to execute the collateral object if the debtor not carrying out the contract, but in practice errors often occur both procedurally and substantially.